Preparation and properties of thermally conductive polyimide/boron nitride composites. Issue 22 (12th February 2016) - Yang, Na; Xu, Chen; Hou, Jun; Yao, Yanmei; Zhang, Qingxin; Grami, Maryam E.; He, Lianqi; Wang, Nongyue; Qu, Xiongwei
Abstract : Hexagonal boron nitride micro particles functionalized by γ-MPS, were used to fabricate PI/BN composites. The thermal conductivity of the composites with 40 wt% m-BN content was increased to 0.748 W m −1 K −1, 4.5 times higher than that of the pure PI. Abstract : Polyimide (PI) has been widely used as a preferred packaging matrix material due to its low dielectricity, outstanding insulation and excellent thermal stability. Hexagonal boron nitride (h-BN) microparticles were functionalized with a silane coupling agent, 3-glycidyloxypropyltrimethoxy silane (γ-MPS), to improve the interface action with the PI matrix. The modified h-BN (m-BN) particles were used to fabricate the PI/m-BN composites with enhanced thermal conductivity by in situ polymerization. The Fourier transform infrared (FTIR) spectra, thermo-gravimetric analysis (TGA), transmission electron microscopy (TEM) and contact angle test proved that γ-MPS coupling agent molecules had been chemically grafted onto the h-BN surface. In addition, the effects of the m-BN content on the thermal conductivity of PI/m-BN composites were investigated. The composite obtained with 40 wt% m-BN particle loading presented a thermal conductivity of 0.748 W m −1 K −1, 4.6 times higher than that of pure PI. Meanwhile, the fabricated PI/m-BN composites retained excellent electrical insulation and thermal stability. The glass transition temperature values of the PI/m-BN composites decreased slightly while the storage modulus improved with the increase of the m-BN content. These results showed that PI/m-BN composites may offer new applications in the microelectronic industry because future substrate materials require effective heat dissipation.